Correlation between various biochemical biomarkers and blood pressure in pregnant women - Kaur, Balwinder; Renu; Kumar, Ashok; Singh, Beant; Kaur, Manjit (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To find out the correlation of C-reactive protein, serum uric acid and serum LDH with hypertensive antenatal patients. Methods: The present study was conducted among preeclamptic and eclamptic antenatal patients. Serum was used for estimation of serum levels of CRP, LDH and Uric acid. The data obtained was compiled and analyzed statistically and was expressed in terms of mean±SD and percentage. Student t-test, Chi-square test, Pearson’s Correlation Coefficient were used and p value less than 0.05 was considered significant. Results: A positive correlation was found between serum CRP level and systolic blood pressure (r = +0.525, P=0.001) & serum CRP level diastolic systolic blood pressure (r= + 0.493, P=0.001). There was a positive correlation between serum uric acid with systolic (r= +0.454, P <0.001) and diastolic blood pressure (r = +0.471, p < 0.001). There was positive correlation between Serum LDH with systolic (r =+0.385, p value of r <0.001) and diastolic BP (r = +0.420, p value of r < 0.001). Conclusion: Hyperuricemia, increased serum CRP and LDH level can be used as biomarkers for identifying women at risk of preeclampsia and its complications along with adverse effects. We conclude that CRP, serum LDH and Serum Uric acid are reliable and inexpensive markers to predict severity of hypertensive disorders of pregnancy.